Pre-clinical and clinical development of the first placental malaria vaccine. (3rd June 2017) - Pehrson, Caroline; Salanti, Ali; Theander, Thor G.; Nielsen, Morten A.
ABSTRACT: Introduction : Malaria during pregnancy is a massive health problem in endemic areas. Placental malaria infections caused by Plasmodium falciparum are responsible for up to one million babies being born with a low birth weight every year. Significant efforts have been invested into preventing the condition. Areas covered : Pub Med was searched using the broad terms 'malaria parasite placenta' to identify studies of interactions between parasite and host, 'prevention of placental malaria' to identify current strategies to prevent placental malaria, and 'placental malaria vaccine' to identify pre-clinical vaccine development. However, all papers from these searches were not systematically included. Expert commentary : The first phase I clinical trials of vaccines are well underway. Trials testing efficacy are more complicated to carry out as only women that are exposed to parasites during pregnancy will contribute to endpoint measurements, further it may require extensive follow-up to establish protection. Future second generation vaccines may overcome the inherent challenges in making an effective placental malaria vaccine.